The role of mutations in the PI3K/AKT/mTOR signal pathway in decreasing ovarian reserve in reproductive patients with deep infiltrative endometriosis - Oxana A. Melkozerova; Ekaterina O. Okulova; Anna A. Mikhelson; Tatyana B. Tretyakova (IP Berlin A.V., 2021)
Aim. To study the effect of deep infiltrative endometriosis on the state of the ovarian reserve in patients of reproductive age, as well as to evaluate the spectrum of mutations in the PIK3CA gene among patients with infiltrative form of external genital endometriosis. Materials and methods. The main group of the study included 50 patients of reproductive age with deep infiltrative endometriosis, in 18 of whom deep infiltrative endometriosis was combined with ovarian endometriomas. The comparison group included 25 patients of reproductive age who underwent laparoscopic metroplasty of an inconsistent uterine scar from a cesarean section. All patients underwent determination of the level of anti-Mllerian hormone, follicle-stimulating hormone and estradiol in the blood by enzyme immunoassay, as well as counting the number of antral follicles in the ovaries during transvaginal ultrasound examination. The search for activating mutations of the PIK3CA gene was carried out by sequencing a new generation of DNA in tissue samples of ovarian endometriomas in patients with a combination of infiltrative endometriosis and endometrioid ovarian cysts (n=18), as well as in biopsies of healthy ovarian tissue in all patients of the main group (n=50) and comparison groups (n=25). Results. When assessing the state of the ovarian reserve in the patients of the two groups, it was found that the anti-Mllerian hormone level in the patient with the infiltration form of external genital endometriosis was 2.62.2 ng/ml, while in the comparison group it was 3.63.5 ng/ml, however, the difference did not reach statistical significance, p0.05. The number of antral follicles according to transvaginal ultrasound was significantly lower in the main group (8.54.5) than in the comparison group (12.24.1), p=0.001. This difference was statistically significant both for patients with ovarian endometriomas (6.04.2, p0.001) and for patients without ovarian endometriomas (9.84.2, p=0.04). Our study did not reveal PIK3CA gene mutations in any of the ovarian endometrioma tissue samples from patients with a combination of infiltrative endometriosis and endometrioid ovarian cysts, as well as in none of the healthy ovarian tissue biopsies from patients of the main group and the comparison group using the new generation DNA sequencing method. Conclusion. The presence of deep infiltrative endometriosis is associated with a decrease in ovarian reserve in patients of reproductive age, regardless of the presence of endometrioid ovarian lesions. Population studies are needed to identify mutations of this gene in endometriosis, as well as to study mutations of other genes encoding proteins regulating the antiapoptotic signaling pathway PI3K/AKT/mTOR, to identify the mechanism of ovarian reserve depletion in infiltrative form of external genital endometriosis.